Influência do ângulo inter-isquiopúbico e sua relação com o espaço isquiofemoral - Urnauer, Luciano (2020)
A cross-sectional study aimed to evaluate the relationship between the inter-ischiopubic angle and the ischiofemoral space in a population of patients without presentation of joint diseases who underwent pelvic magnetic resonance imaging (MRI) by means of consecutive sampling of individuals who underwent an image study in the Diagnostic Imaging Center of Hospital São Lucas da PUCRS between January 2017 and December 2018. The data analyses from MRI scans of the pelvis were carried out by two blinded evaluators for quantification and morphological analysis and measurement of the distance between the ischiofemoral space and the inter-ischiopubic angle. The data from this study showed a very good agreement between observers in relation to the measures evaluated, and the correlations between the inter-ischiopubic angle and the ischiofemoral space tend to be more consistent in relation to the schiatic angle in male subjects.